Metabolic Profile and Performance Responses of Ranunculus asiaticus L. Hybrids as Affected by Light Quality of Photoperiodic Lighting - Carillo, Petronia; Dell’Aversana, Emilia; Modarelli, Giuseppe Carlo; Fusco, Giovanna Marta; De Pascale, Stefania; Paradiso, Roberta (Frontiers in Plant Science, 2020)
R. asiaticus is a quantitative long day plant grown for cut flowers and flowering potted plants production. We evaluated the influence of light spectrum of three light sources for end-of-day photoperiodic treatments, with different phytochrome photoequilibria (PPE) induced at plant level, on metabolic profiling of two hybrids of Ranunculus asiaticus L., MBO and MDR, in plants from vernalized tuberous roots. The following treatments were compared to natural day length (NL): white fluorescent light (FL, PPE 0.84), LEDs Red:Far Red light at 3:1 ratio (R:FR 3:1, PPE, 0.84), and LEDs Red:Far Red light at 1:3 ratio (R:FR 1:3, PPE 0.63). Measurements were carried out to evaluate the time course of carbohydrate, amino acid and protein levels throughout the growing cycle in tuberous roots and leaves, in relation to the different plant stages (pre-planting, vegetative phase and flowering). The study of metabolic profiling suggested that the differences between the tuberous root reserves of the two R. asiaticus hybrids could be responsible for the capacity of MBO to exert an early flowering. In particular, the proton-consuming synthesis during pre-planting of two amino acids, alanine and  aminobutyric acid (GABA), is able to buffer the cytoplasmic acidosis and pH altered by the vernalization process, and GABA istself can efficiently scavenge reactive oxygen species. This fast response to the stress caused by vernalization allows MBO plants to accelerate the process of vegetative development and flowering. Some other changes in metabolites profile were certainly related to the different response to day length and photoperiodic light quality in the two hybrids, like dose exerted by low R:FR lighting in both MBO and MDR. However, the most of responses are under a strict genetic control.